Effect of tool pin profile on performance of friction stir welding of brass-copper-based butt welded joint. (2016) - Sekhon, Sukhwinder Singh; Kumar, Harmesh; Sehgal, Shankar
In the present research work, industrial grade pure copper and brass have been joined using friction stir welding. Effect of tool pin profile along with stirrer rotation speed and welding speed on the friction stir welding performance in terms of breaking load and percentage elongation has been investigated. Three tool pin profiles were designed viz., cylindrical, tapered threaded and square. These were used to fabricate the joints at three different rotation speeds (1, 000, 1, 100, 1, 200 rpm) and welding speeds (25, 35, 40 mm/min.). The experiments were designed according to Taguchi-based L-9 orthogonal array. Variance analysis has been carried out to obtain the influence and percentage contribution of process parameters on welding performance. Optimisation results reveal that most significant factor is the pin profile. Square pin profile at 1, 200 rpm along with 35 mm/min welding speed produces mechanically sound and metallurgically defect-free weld joints.